DESAIN PELAT BETON BERPORI DENGAN POLIKARBONAT - Nurtanto, Dwi; Hasanuddin, Akhmad (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Porous concrete which became one of the solutions in pavement construction and is a product that can be said to be successful in meeting the expectations as environmentally friendly construction. Polycarbonate is a thermoplastic polymer group, is formed by applying heat. This type of plastic is used widely in the chemical industry today. Plastic has many advantages, namely thermal resistance compared with other types of plastic, resistant to impact, and very clear. Research "Design of Porous Slab Concrete with Polycarbonate" as a solution in the construction of permeable pavement or impervious to the reservoir and is a product that can be expected as environmentally friendly construction. Examples of permeable pavement is existing streets in residential areas, sidewalks, parking lots, and park area. In this study will be made slab with thickness of 5 cm, width 40 cm length 40 cm of porous concrete which is used in making sheets of polycarbonate  pores and porous concrete slab is expected to have a compressive strength and flexural high enough and friendly environment. As an outcome of this study is expected porous slab is used for road pavement, parking lot, residential or rural road vehicle load is not heavy intensity. The results of the study with a polycarbonate porous concrete slab can be summarized as follows: Plates are ideal for porous plate is polycarbonate plate with a distance of 8 cm, which is similar to the strong bending without polycarbonate slab and permeability is also good.